2014
DOI: 10.1080/10407782.2014.915685
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Heat Transfer from Sudden Expansion Using Nanofluid

Abstract: Conjugate heat transfer from sudden expansion using nanofluid is studied numerically. The governing equations are solved using unsteady stream function-vorticity formulation method. Results are compared with zero nanoparticle fluid to exhibit the role of nanoparticle. The effect of volume fraction of nanoparticles and type of nanoparticles on heat transfer are examined and found to have a significant impact. Local Nusselt number and average Nusselt number are reported in connection with various nanoparticle, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 43 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…For the purpose of validation of the developed code (FORTRAN code), the results obtained in the present research are compared with the simulation results of Abu-Nada 33 and Kanna et al . 34 . Reattachment length (X r ) and local maximum Nusselt number obtained at Re = 200 for Cu nanoparticles are regarded as parameters for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of validation of the developed code (FORTRAN code), the results obtained in the present research are compared with the simulation results of Abu-Nada 33 and Kanna et al . 34 . Reattachment length (X r ) and local maximum Nusselt number obtained at Re = 200 for Cu nanoparticles are regarded as parameters for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Table 6 shows the comparison of reattachment length obtained by the present research and those reported by Abu-Nada 33 and Kanna et al . 34 for 5% and 20% volume fractions of Cu nanoparticle. It is noted that the present numerical results compare with the results of the above authors with maximum of 8% error.…”
Section: Resultsmentioning
confidence: 99%
“…Most numerical studies consider confined/non-confined laminar swirling jet simulations a steady problem, [31][32][33] despite unsteady mechanics may appear, as will be demonstrated in this work. The increasing interest in nanofluids, because of their special thermophysical properties, is also found in novel works such as, 34 where conjugate heat transfer in an expansion ratio of 2 with a nonswirling nanofluid flow is simulated to increase notably the thermal efficiency of the mechanism, 35 or where it is reported that the eddy formation in the expansion is reduced by the increase in nanoparticle fraction. The latest works on the topic of expanded swirling flows are mostly related to turbulent flows.…”
Section: Introductionmentioning
confidence: 99%